Household Financial Management and the Welfare Level of Coastal Communities in Pasar Sorkam Village, Tapanuli Tengah - Mansur Tanjung; Riwayani; Delita Sihotang; Yenni Sofiana Tambunan; Diana Maya Sari (International Journal of Marine Engineering Innovation and Research, 2026)
Communities that are still considered poor often identify with fishermen's households. This impression arises due to the simple condition of their houses and a lifestyle that often appears unbalanced between their income and expenses. This research focuses on exploring the level of welfare of the Pasar Sorkam community in Tapanuli Tengah from the aspect of their household financial management. The research employs a mixed methodology approach, supported by measurements of the community's welfare index. The research results indicate that the income level of the fishing community is classified as low, while the expenditure level is high. The fishing community in Pasar Sorkam Village has a welfare index value of 55.6, indicating that they fall into the low welfare category. The research is expected to serve as a reference for relevant future studies and as a guideline for policy formulation for the local government of Tapanuli Tengah Regency.